Learning languages? Why bother, when there’s google translate? Reflections on the future from the inspector’s point of view - Lorenzo Galés, María Nieves (Avances en Supervisión Educativa, 2014)
Foreign language learning in academic environments is now tied to methodological approaches that are  interdisciplinary (CLIL, PBL), integrated (ILT-Integrated Learning Technologies), connectivist (ICT and CLT) and pre-profesionalized (Blended, Apprenticeship), in an attempt to contextualize  language teaching and to facilitate the development of linguistic and communicative skills, beyond the world of Google Translate. New methodological tools are emerging in the classroom: Flipped Classrooms, Inquisitive Minds, Design Thinking, Problem Solving... What does the inspectorate of education need to know to ensure quality intervention in the classroom, the school and the territory? This communication reflects on context, and we propose specific lines of action  to enhance the role of the Inspectorate in this area.
Keywords: language instruction; plurilingualism; multilingualism; cognition; foreign languages; bilingual education; educational policy; second language instruction